On Programmed Cell Death in Plasmodium falciparum: Status Quo - Dewaldt Engelbrecht; Pierre Marcel Durand; Thérèsa Louise Coetzer (Journal of Tropical Medicine)
Conflicting arguments and results exist regarding the occurrence and phenotype of programmed cell death (PCD) in the malaria parasite Plasmodium falciparum. Inconsistencies relate mainly to the number and type of PCD markers assessed and the different methodologies used in the studies. In this paper, we provide a comprehensive overview of the current state of knowledge and empirical evidence for PCD in the intraerythrocytic stages of P. falciparum. We consider possible reasons for discrepancies in the data and offer suggestions towards more standardised investigation methods in this field. Furthermore, we present genomic evidence for PCD machinery in P. falciparum. We discuss the potential adaptive or nonadaptive role of PCD in the parasite life cycle and its possible exploitation in the development of novel drug targets. Lastly, we pose pertinent unanswered questions concerning the PCD phenomenon in P. falciparum to provide future direction.